Response of planktonic diversity and stability to environmental drivers in a shallow eutrophic lake - Yue Geng; Meixia Li; Ruihong Yu; Heyang Sun; Linxiang Zhang; Liangqi Sun; Changwei Lv; Jifei Xu (Ecological Indicators, 2022)
Plankton is an important component of a healthy shallow lake aquatic system, and the diversity and stability of its community structure are impacted by numerous environmental factors. However, knowledge about the relative importance of these factors is limited. This study presents a case study conducted in semi-arid, shallow eutrophic lakes in China to evaluate the relative importance of physical, chemical, and nutritional characteristics of water quality and light effects on the spatiotemporal distributions of diversity and stability of plankton communities. The findings showed that the plankton community was the least diverse in winter and the most stable during the spring-to-summer transition. The results of partition variation showed that physical and chemical indicators, nutritional parameters, and light effects explained >70 % of the zooplankton community dynamics, compared with 37 % for phytoplankton. For phytoplankton community composition, physical and chemical parameters, followed by light, had the greatest influence. Further analysis showed that phytoplankton were influenced primarily by nutrients, water depth, and pH. Similarly, the diversity and stability of the zooplankton exhibited physical and chemical parameter responses, and the influence of nutrients also played a significant role. Structural equation modelling showed that light had minimal direct effect on the plankton and affected the plankton indirectly through changes in total nitrogen and NO3-N. This study estimates the distribution of plankton community in a shallow eutrophic lake, quantifying the relative effects of different environmental drivers on plankton diversity and stability, and provides an in-depth understanding for improving the lake water quality and controlling nutrients pollution.